2005
DOI: 10.1073/pnas.0506570102
|View full text |Cite
|
Sign up to set email alerts
|

Friend spleen focus-forming virus transforms rodent fibroblasts in cooperation with a short form of the receptor tyrosine kinase Stk

Abstract: Friend spleen focus-forming virus (SFFV) causes rapid erythroleukemia in mice due to expression of its unique envelope glycoprotein, gp55. Erythroid cells expressing SFFV gp55 proliferate in the absence of their normal regulator erythropoietin (Epo) because of constitutive activation of Epo signal transduction pathways. Although SFFV infects many cell types, deregulation of cell growth occurs only when SFFV infects erythroid cells, suggesting that these cells express unique proteins that the virus requires to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…21 Furthermore, our previous data indicated that a deletion mutant in which the N-terminal extracellular domain (55 aa) of sf-Stk was deleted was unable to transform SFFV-P-and SFFV-A-infected NIH3T3 cells. 23 Therefore, the extracellular sequences of sf-Stk are crucial for efficient transformation of fibroblasts by SFFV. In this study, we constructed 10 continuous deletion mutants within a 55 amino acid stretch of the sf-Stk N-terminal extracellular domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…21 Furthermore, our previous data indicated that a deletion mutant in which the N-terminal extracellular domain (55 aa) of sf-Stk was deleted was unable to transform SFFV-P-and SFFV-A-infected NIH3T3 cells. 23 Therefore, the extracellular sequences of sf-Stk are crucial for efficient transformation of fibroblasts by SFFV. In this study, we constructed 10 continuous deletion mutants within a 55 amino acid stretch of the sf-Stk N-terminal extracellular domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…293T cells, NIH3T3 cells, SFFV-P/NIH3T3 and SFFV-A/ NIH3T3 23 (transfected with SFFV-P and SFFV-A, respectively) were cultured in Dulbecco's minimal essential medium supplemented with 10% fetal calf serum.…”
Section: Cellsmentioning
confidence: 99%
See 3 more Smart Citations